Doubling the Dose of Bevacizumab Beyond Progression in Metastatic Colorectal Cancer–the Experience of a Tertiary Cancer Center - Căinap, Călin; Bochiş, Ovidiu-Vasile; Vlad, Cătălin; Popita, Raluca; Achimaş-Cadariu, Patriciu; Havasi, Andrei; Vidrean, Andreea; Dranca, Alexandra; Piciu, Andra; Constantin, Anne-Marie; Tat, Tiberiu; Dana, Maniu; et al. (Frontiers in Pharmacology, 2021)
Background: Colorectal cancer (CRC) is the third most common cancer in Europe, with an annual increase in incidence ranging between 0.4 and 3.6% in various countries. Although the development of CRC was extensively studied, limited number of new therapies were developed in the last few years. Bevacizumab is frequently used as first- and second-line therapy for management of metastatic CRC (mCRC). The aim of this study is to present our experience with using bevacizumab beyond disease progression at different dosage levels in mCRC patients, in terms of overall survival, progression-free survival, time to treatment failure, and toxicities. Methods: We performed a consecutive retrospective analysis of patients with confirmed mCRC who were treated with bevacizumab at "Prof Dr. Ion Chiricuta" Institute of Oncology, Cluj-Napoca, Romania. We included patients who had received bevacizumab as first- or second-line therapy and further stratified them according to the dose administered as a second-line (either standard dose of 5 mg/kg every 2 weeks or 7.5 mg/kg every 3 weeks, or double dose of 10 mg/kg every 2 weeks or 15 mg/kg every 3 weeks–depending on the classical chemotherapy partner). All patients had received bevacizumab beyond progression (BYP) which is defined as continuing bevacizumab administration through second-line treatment despite disease progression. In each group, we evaluated the prognostic factors that influenced survival and treatment outcome. Results: One hundred and fifty-one (151) patients were included in the study. Themedian age of patients receiving double dose bevacizumab (DDB) and standard dose bevacizumab (SDB) was 58 years (range 41–71) and 57 years (range 19–75), respectively. The median overall survival in the DDB group was 41 months (range 27–49) compared to 25 months (range 23–29) in the SDB group (p = 0.01 log-rank test). First-line oxaliplatin-based treatment was used more frequently regardless of group, while irinotecan-based more frequently used as a second-line treatment (p = 0.014). Both oxaliplatin- and irinotecan-based regimens were found to be suitable partners for BYP. Statistical analysis revealed that dose intensity, primary tumor location, and cumulative exposure to BYP had significant influence on survival. Conclusion: Doubling the dose of bevacizumab after first progression may improve survival in mCRC patients. Increasing bevacizumab dose intensity could override the prognostic impact of primary tumor location in patients receiving double the dose of bevacizumab after first disease progression.